CONTROL GERENCIAL: EL ANÁLISIS DEL COSTEO VARIABLE Y ABSORBENTE COMO HERRAMIENTA DE GESTIÓN - Aguero del Carpio, Lizardo (2005)
The Organizations, being in a competitive and turbulent world, are opting for looking toward inside, in an introspective attitude, obviously, without neglecting their attention to the client, or what is known as the Relational Function with the Client of the Customer Relationship Management (CMR). For that reason it is of vital importance, to know the Internal Structure of the Costs of the organizations, and the handling of the same ones, those which evidently will rebound in the price and in the profitability of the organizations. It is so the treatment of the direct or variable costs, valuable tool that includes in the structure of the costs only those costs or variable expenditures in the production of the product or benefit of services. The costs for absorption that include the structure of the costs are both the variable costs and the fixed ones, in determining the unitary costs of production